Publicidad, propaganda y poder. - Jácome Cicenia, Alex Francisco (2015)
This paper presents the possibility of an unprecedented social change, based on the mental emancipation of societies through the progressive acquisition of knowledge, against the hegemonic power represented by corporations, governments, political and economic power that supports it, using propaganda information distortion, primarily, as well as designing and implementing educational policies that have limited the human being in its fullness. There is evidence that technology and the development of digital resources have led to the incursion of the media in the virtual environment and the emergence of communication actors making available to the masses, matters previously banned, enabling the possibility of breaking with concepts such as eurocentrism, evolution and creation, according to whom the issue, efforts to disseminate the apparent democracy through war or the idea that human beings are the pinnacle of evolution at the expense of the natural world, among many others, who for centuries have been disseminated to the general population with the letterhead of the accepted truth only partially supported by the results of scientific research , ethically challenged and still are today reinforced by the different levels of power according to an alternative orientation and a globalized scale. At the same time, because of accessibility and content production on blogs, web pages and digital and alternative media, it has been paved the way to the possibility of breaking with concepts spread for centuries. As a consequence, a new state of consciousness has been created growing exponentially in order to reorganize power.